The influence of FOMC member characteristics on the monetary policy decision-making process - Smales, Lee; Apergis, N. (2016)
This paper provides new empirical evidence on a monetary policy committee with heterogeneous members whose decisions affect the efficacy of monetary policy. It thereby provides a link between the literature on monetary policy committees and central bank monetary policy implementation through monetary rules. Using a novel dataset of the idiosyncratic characteristics of FOMC members, over the period from August 1979 to February 2014, the empirical findings show that characteristics such as education, age, and, to a lesser extent, work experience are not important in understanding the FOMC decision-making process. Instead, the results point to the importance of time spent within the Federal Reserve System, tenure on the FOMC itself, and the influence of the Chair in shaping the decision-making process. The results are expected to have implications for the capacity of economic agents, as well as various markets in the economy, to more readily interpret public (monetary policy) information that reaches them. This makes the monetary policy decision process less noisy and thus enhances the capability of agents and markets to attach the correct weight to this information.